HEPATOPROTECTIVE EFFECTS OF BROWN ALGAE PADINA TETRASTROMATICAAGAINST CARBON TETRACHLORIDE INDUCED HEPATOXICITY - CLARA GNANA SELVI B,; PANNEERSELVAM A,; AMUTHA SANTHANAM, (International Journal of Pharma and Bio Sciences, 2014)
The main objective of this study was to investigate the antioxidant and hepatoprotective effects of brown algae Padina tetrastromatica against carbon tetrachloride using animal model mice. Carbon tetrachloride is an organic liquid similar to chloroform. The hepatoprotective effect was assessed by monitoring the serum marker enzymes, antioxidants like thiobarbituric acid, superoxide dismutase, catalase, glutathione peroxidase, glutathione-s-transferase, and protein. The animal groups were divided into four includes Group I Normal mice, Group II Mice treated with Olive oil, Group III treated with Carbon tetrachloride along with olive oil (1:1 (v/v) mixture of CCl4 and olive oil), Group IV treated with both Carbon tetrachloride and of Padina tetrastromatica extract. The seaweed extract was administered three hours after the administration of carbon tetrachloride. In order to assess the hepatic damage in liver, the activities of Thiobarbituric acid, Glutathione, and Superoxide dismutase, Catalase and Glutathione peroxide were estimated in animal model. Padina tetrastromatica extract produced significant (P<.001) hepatoprotective effects by decreasing the activity of serum enzymes and bilirubin. Based on the histopathological and biochemical parameters, it was suggested that Padina tetrastromatica extract could perhaps protect liver cells from carbon tetrachloride induced liver damage by its antioxidant effect of hepatocytes thus decreasing the harmful effects of toxic metabolites of carbon tetrachloride.